puffandclim
puffandclim
01-02-2018
Mathematics
contestada
Solve for y: 2(3y-4)=3(y-2/3)
Respuesta :
raulnhurtado
raulnhurtado
01-02-2018
2*(3*y-4) = 3*(y-(2/3)) // - 3*(y-(2/3))
2*(3*y-4)-(3*(y-(2/3))) = 0
2*(3*y-4)-3*(y-2/3) = 0
2*(3*y-4)-3*(y-2/3) = 0
3*y-6 = 0
3*y-6 = 0
3*y-6 = 0 // + 6
3*y = 6 // : 3
y = 6/3
y = 2
y = 2
Answer Link
VER TODAS LAS RESPUESTAS ( 67+ )
Otras preguntas
Who was the first president in Mexico?
Tubaugh Corporation has two major business segments--East and West. In December, the East business segment had sales revenues of $360,000, variable expenses of
Which condition causes storms to occur? A. freezing of water droplets B. sudden change in air pressure C. condensation of water vapor D. rapid heating of upper
Which of the following will NOT shift the aggregate supply curve to the left? a decrease in corporate taxes an increase in the minimum wage an increase in the l
Please write your own sentence using the word deficit.
An airline knows that there are two types of travelers: business travelers and vacationers. For a particular flight, there are 100 business travelers who will p
Complete the table for the given rule y=5x
5. Suppose that a particular candidate for public office is in fact favored by p = 48% of all registered voters. A polling organization is about to take a simpl
which expression is equivalent to 3x/5 a: 15x/20 b: 12x/20 c: 12x/5
How did Congress attempt to maintain a balance of power between Northern and Southern states in the mid-1800s?